Overview of Prescription Opioid Deaths in the Oklahoma State Medicaid Population, 2012–2016. Issue 8 (August 2018) - Pham, Timothy T.; Skrepnek, Grant H.; Bond, Christopher; Alfieri, Thomas; Cothran, Terry J.; Keast, Shellie L.
Abstract : Background: Medicaid members are predisposed to unintentional prescription opioid overdose. However, little is known about their individual risk factors. Objectives: To describe demographic and clinical characteristics, medical utilization, opioid use, concurrent use of benzodiazepines, risk factors, and substances involved in death for Oklahoma's Medicaid members who died of unintentional prescription opioid poisoning. Subjects: Decedents who were Medicaid eligible in Oklahoma during the year of death, had an opioid recorded in cause of death, and had ≥1 opioid prescription claim between January 1, 2011 and June 30, 2016 were cases. Controls were living Medicaid members and were matched 3:1 to cases through propensity score matching. Measures: Demographics, clinical characteristics, and medical/pharmacy utilization were examined in the 12 months before the index date. Results: Of 639 members with fatal unintentional prescription opioid overdoses, 321 had ≥1 opioid prescription claim in the year before death; these were matched to 963 controls. Compared with controls, decedents had significantly greater proportions of nonopioid substance use disorders, opioid abuse/dependence, hepatitis, gastrointestinal bleeding, trauma not involving motor vehicle accidents, nonopioid poisonings, and mental illness disorders. Decedents had significantly higher daily morphine milligram equivalent doses (67.2±74.4 vs. 47.2±50.9 mg) and greater opioid/benzodiazepine overlap (70.4% vs. 35.9%). Benzodiazepines were involved in 29.3% of deaths. Conclusions: Several comorbidities indicative of opioid use disorder and greater exposure to opioids and concomitant benzodiazepines were associated with unintentional prescription opioid overdose fatalities. Prescribers and state agencies should be aware of these addressable patient-level factors among the Medicaid population. Targeting these factors with appropriate policy interventions and education may prevent future deaths. Abstract : Supplemental Digital Content is available in the text.